Earliest Dates of Microlithic Industries (42-25 ka) from West Bengal, Eastern India: New Light on Modern Human Occupation in the Indian Subcontinent. - BASAK, Bishnupriya; SRIVASTAVA, Pradeep (Asian Perspectives: Journal of Archeology for Asia & the Pacific, 2017)
Ancient microliths in South Asia have now been dated at least as early as 42-25 thousand years ago (ka), specifically at Mahadebbera and Kana, situated in the West Bengal area of India. This information adds substantively to scientific understanding of early human migrations and significant technological developments during the Pleistocene. Dating was possible through Optically Stimulated Luminescence (OSL) and the associated microliths and other artifacts were examined in detail. In relation to prior findings in the larger surrounding region, the new discoveries allow discussion of raw materials acquisition, possible travel routes, and other issues during a critical time of human evolutionary history.